2002
DOI: 10.1128/jb.184.18.5174-5178.2002
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Expression of theilv-leuOperon Encoding Enzymes of Branched-Chain Amino Acid Biosynthesis Limits Growth of aBacillus subtilis ccpAMutant

Abstract: Bacillus subtilis ccpA mutant strains exhibit two distinct phenotypes: they are defective in catabolite repression, and their growth on minimal media is strongly impaired. This growth defect is largely due to a lack of expression of the gltAB operon. However, growth is impaired even in the presence of glutamate. Here, we demonstrate that the ccpA mutant strain needs methionine and the branched-chain amino acids for optimal growth. The control of expression of the ilv-leu operon by CcpA provides a novel regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
69
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 24 publications
2
69
0
Order By: Relevance
“…The results of the transcriptome and proteome analyses described above imply various connections of central control of carbon metabolism with various metabolic networks, but the sections below deal only with networks connecting the control of carbon metabolism with other metabolic regulation that has been experimentally verified. Also, it is notable that a CcpA-defective mutant of B. subtilis grows at a slower rate in minimal medium with glucose and ammonium as carbon and nitrogen sources than wild-type cells, 98) which indicates an intimate connection between catabolism and anabolism, as described below. The resulting metabolic networks mediated by CcpA are illustrated in Fig.…”
Section: Metabolic Network Mediated By Ccpamentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the transcriptome and proteome analyses described above imply various connections of central control of carbon metabolism with various metabolic networks, but the sections below deal only with networks connecting the control of carbon metabolism with other metabolic regulation that has been experimentally verified. Also, it is notable that a CcpA-defective mutant of B. subtilis grows at a slower rate in minimal medium with glucose and ammonium as carbon and nitrogen sources than wild-type cells, 98) which indicates an intimate connection between catabolism and anabolism, as described below. The resulting metabolic networks mediated by CcpA are illustrated in Fig.…”
Section: Metabolic Network Mediated By Ccpamentioning
confidence: 99%
“…119) Besides the probable necessity that the CcpA-dependent CCA of ilv-leu in glycolysis proceed continuously for the draining of accumulated pyruvate, it is notable that this positive regulation links carbon metabolism to amino acid anabolism. Recent global gene expression studies on amino acid availability 120) and CodY regulation, 121) as well as on the metabolic links of ilv-leu expression to glucose and nitrogen metabolism, 38,39,98,122) indicate that the ilv-leu operon is under direct negative transcriptional control through two major global regulators of nitrogen metabolism (CodY and TnrA).…”
Section: Metabolic Network Mediated By Ccpamentioning
confidence: 99%
“…Genes of very important metabolic pathways are regulated by CcpA, such as citB and citZ contributing to the Krebs cycle (Kim et al, 2002), gltAB for ammonium assimilation (Faires et al, 1999) or the ilv-leu operon for branched-chain amino-acid biosynthesis (Ludwig et al, 2002). Other studies revealed that CcpA in Gram-positive bacteria also regulates carbon catabolite activation (CCA) of acetoin secretion, acetate biosynthesis genes in B. subtilis (Turinsky et al, 2000) and glycolytic genes in B. subtilis, Lactococcus lactis and Enterococcus faecalis (Luesink et al, 1998;Leboeuf et al, 2000;Ludwig et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, inactivation of ccpA is known to have a strong effect on growth rate (Miwa et al, 1994;Hueck et al, 1995;Monedero et al, 1997;Leboeuf et al, 2000). This growth defect in B. subtilis has been proposed to be related to lack of expression of the above-mentioned gltAB operon, encoding glutamate synthase, necessary for ammonium assimilation (Faires et al, 1999), and the ilv-leu operon (Ludwig et al, 2002).In Bacillus megaterium, four single mutations in CcpA were described that showed independent effects on growth and CCR (Küster et al, 1999a): three mutations showed no CCR but normal growth and one was solely defective in growth. All of these mutations are located within the N-terminal DNA-binding domain (DBD) of CcpA.…”
mentioning
confidence: 99%
“…Glucose can also activate proHJ expression via CcpA (CJ Lin and GC Shaw, unpublished observations). The biological significance for CcpA-mediated glucose activation of the gltAB operon or the ilvB operon was previously suggested to be a link between carbon and nitrogen metabolism [8,14]. The physiological significance for CcpA-mediated glucose activation of degU was postulated to be relevant with consumption of acetyl-coenzyme A during polyketide synthesis [11].…”
Section: Introductionmentioning
confidence: 99%